"My village fell apart": Parents' Views on Seeking Informal Mentoring Relationships for Their Children. Issue 5 (7th April 2020) - Weiler, Lindsey M.; Keyzers, Angela; Scafe, Meredith; Anderson, Amber; Cavell, Timothy A.
Abstract : Objective: To assess parents' perceptions of barriers and facilitators to promoting informal mentoring relationships for their children with caring adults in their existing social network. Background: Supportive relationships with nonparental adults are critical to positive youth development, social capital, healthy living, and upward mobility, but not all children experience such relationships. Because parents are the primary gatekeepers to children's social networks, we presumed that parents could play a role in shaping children's informal mentoring relationships. Method: We conducted eight focus groups and used a semistructured interview to ask participants about mentoring and potential barriers or facilitators to connecting children with informal mentors. Participants were 55 parents/caregivers ( M age = 41.43 years; 96.4% female; 77.9% unmarried). Results: Parents were open to the involvement of nonparental adults in children's lives, but they differed in the extent to which their social network offered viable mentor candidates. Other barriers included feeling too proud to ask for help and concerns that informal mentors would be unsafe or inconsistent. Facilitative factors included appreciating the benefits of informal mentoring relationships, feeling connected to one's community, and being able and willing to ask for help in the face of doubt or fear. Conclusion: Parents were generally positive about children receiving support from informal mentors and acknowledged the potential role they could play in forming those connections; they also recognized potential barriers to making those connections. Implications: Parents' perception about their "village" suggests the need to develop and evaluate programs that help parents connect children with supportive informal mentors.